2007
DOI: 10.1111/j.1745-7262.2007.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased oxidative damage of sperm and seminal plasma in men with idiopathic infertility is higher in patients with glutathione S-transferase Mu-1 null genotype

Abstract: Our results suggest that the susceptibility of sperm and seminal plasma to oxidative stress is significantly greater in idiopathic infertile men with the GSTM1 null genotype compared with those possessing the gene. Therefore, in patients with idiopathic infertility, GSTM1 polymorphism might be an important source of variation in susceptibility of spermatozoa to oxidative damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 33 publications
(38 reference statements)
5
65
1
1
Order By: Relevance
“…The characteristics of selected studies are summarized in Table 1. A total of 12 eligible studies met the inclusion criteria, including 11 studies for GSTM1 [14,15,[25][26][27][28][29][30][31][32][33] and 9 ones for GSTT1 [17,26,27,[29][30][31][32][33]. All the included studies were case-control studies.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of selected studies are summarized in Table 1. A total of 12 eligible studies met the inclusion criteria, including 11 studies for GSTM1 [14,15,[25][26][27][28][29][30][31][32][33] and 9 ones for GSTT1 [17,26,27,[29][30][31][32][33]. All the included studies were case-control studies.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…Published studies are available on the association of genotype in GSTM1, GSTT1 genes and idiopathic male infertility. GSTM1 polymorphism might be an important source of variation in susceptibility of spermatozoa to oxidative damage in patients with idiopathic infertility [14]. GSTT1 has functional polymorphisms that result in the virtual absence of enzyme activity [13].…”
Section: Introductionmentioning
confidence: 99%
“…21 Inconsistent studies are available on the association of polymorphism in GSTM1, GSTT1 and GSTP1 genes and idiopathic male infertility. Aydemir et al 22 reported that in patients with idiopathic infertility, GSTM1 polymorphism might be an important source of variation in susceptibility of spermatozoa to oxidative damage. In a study conducted in Russian men, Polonikov et al 23 reported that the nondeletion genotype of the GSTT1 gene is strongly associated with the increased risk of idiopathic male infertility and asthenozoospermia.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 30% of men seeking treatment for their infertility present no demonstrable etiology and their condition remains idiopathic (Pasqualotto and Pasqualotto, 2006). It is a heterogeneous disorder, with several genetic and environmental factors contributing to impaired spermatogenesis (Aydemir et al, 2007). Studies revealed a significant decline in human semen quality and quantity over the past decades, and the increasing occurrence of disorders of the male reproductive tract is yet unknown.…”
Section: Introductionmentioning
confidence: 99%